PENYEBARAN LUBANG GEREK SERANGAN RINTISAN KUMBANG AMBROSIA PADA DOLOK KARET YANG DIKULITI - Paimin Sukartana (Jurnal Penelitian Hasil Hutan, 1989)
The  distribution    of  initial  tunnel  of  ambroisa  beetle  infestations   on debarked   rubber  logs was studied.    The  surface. of  the  test  logs  was plotted   into  8 equal   beds,   including   two  single  beds situated  on  the  top  and bottom,  and three pair- ed  others  situated   on  the  upper  sides,   sides,  and  under  sides. Intensity  of  the  beetle  tunnels  on  each bed  was observed  four  times  at  the  day  of  11,  13,   17, and  21 after  the  debarking.It  was shown   that  the  ambrosia   beetle  tunnels   were  not  equally  scattered   on  the  entire  parts  of  the  log  surface.The  two  paired  plots,   sides  and   upper  sides,  were  most  susceptible   ones  eventhough   the  intensity    of the  tunnels  vari- ed  during  the  observation   periods.    The   lower  susceptible   plots   were  respectively   recorded  on  the  top,  under  sides and bottom   part  of  the  logs.